Reversible deprotonation as crucial step in bispidine copper-catalyzed aziridination reaction - Josephy, Thomas; Heiduk, Markus; Saxl, Tobias; Bleher, Katharina (Inorganica chimica acta, 2025)
Copper nitrene complexes are highly reactive species and known as active intermediates in copper-catalyzed C-H amination and aziridination. In this study, we investigated the reaction mechanism of a bispidine-based copper complex with a secondary amine in the selective aziridination of styrene using [N-(p-toluenesulfonyl)imino]phenyliodinane as oxidant. It was demonstrated that the addition of Et3N to the reaction mixture facilitates a reversible deprotonation throughout the catalytic cycle, contributing to an overall accelerated product formation. Additionally, the use of two pentadentate ligands with secondary amines in combination with two tertiary methyl-amine ligands showed that the positioning of the secondary amine trans to the nitrene group is crucial for observing an increase of the turnover frequency. Furthermore, through the addition of radical quenchers and the investigation of additional substrates, a copper(II) radical nitrene intermediate was postulated, which concludes substrate conversion via a stepwise reaction mechanism.